Nematophagous fungi as biological control agents of parasitic nematodes in soils of wildlife parks - Christopher Sander; Stephan Neumann (International Journal for Parasitology: Parasites and Wildlife)
Infections with soil-transmitted helminths pose a significant threat to wildlife in enclosures, where transmission of these parasitic larvae is easier due to the limited space. Nematophagous fungi offer a promising solution as they can naturally control these nematodes. In this study, three nematophagous fungi (Arthrobotrys oligospora, Dactylaria scaphoides, Nematoctonus leiosporus) purchased from the non-profit global biological resource center ATCC were tested for their suitability as biological control agents. The nematodes Strongyloides sp., Trichostrongylus sp. and Oesophagostomum sp. Were isolated from three animal species: wild boar (Sus scrofa) (n = 10), fallow deer (Dama) (n = 5) and mouflon (Ovis orientalis musimon) (n = 5) from a wildlife park using the Baermann-Wetzel method. In a second step, the fungi were brought into contact with the parasites on the soil of the enclosures. The two media tests showed that the nematophagous fungi were more effective on the agar plate than on the autoclaved soil. Only D. scaphoides showed good efficacy on both media, while the other two fungi showed more marked differences on the two media. The results showed that these three nematophagous fungi can reduce parasites in soil before they are ingested by an infected animal. Given the increasing development of drug resistance and the use of chemical agents for soil treatment, this is an important finding that should be pursued in the future.